2009
DOI: 10.1200/jco.2008.17.7568
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of an Outpatient Palliative Care Intervention in Patients With Metastatic Cancer

Abstract: This phase II study demonstrates efficacy of an OPCC for improvement of symptom control and patient satisfaction with care. Randomized controlled trials are indicated to further evaluate the effectiveness of specialized outpatient palliative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
143
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(153 citation statements)
references
References 49 publications
5
143
1
4
Order By: Relevance
“…The interval of 6 days between referral and death in this sample of patients with acute leukemia is similar to that reported in retrospective studies of patients with hematological malignancies, which have reported intervals between referral and death of 2 weeks or less [18,19]. There is increasing evidence of the benefit of early palliative care in patients with metastatic cancer [11][12][13][14][15]. Models of palliative and supportive care, designed specifically for patients with acute leukemia, may be useful to support patients through the symptoms and distress associated with intensive treatment, and potentially to the end of life.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The interval of 6 days between referral and death in this sample of patients with acute leukemia is similar to that reported in retrospective studies of patients with hematological malignancies, which have reported intervals between referral and death of 2 weeks or less [18,19]. There is increasing evidence of the benefit of early palliative care in patients with metastatic cancer [11][12][13][14][15]. Models of palliative and supportive care, designed specifically for patients with acute leukemia, may be useful to support patients through the symptoms and distress associated with intensive treatment, and potentially to the end of life.…”
Section: Discussionsupporting
confidence: 61%
“…There has been recent acknowledgment of the relevance of palliative care for patients with hematological malignancies [10], and accumulating evidence of the benefit of palliative care when provided concurrently with curative or life-prolonging treatment [11][12][13][14][15]. However, there have been no prospective studies assessing referral to palliative care and psychosocial services for patients with acute leukemia and correlating these data with symptom severity.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, palliative care has been delivered late in the disease course, 1 as physicians tend to perceive palliative care (PC) as the alternative to life-prolonging or curative care. Studies suggest that late referrals to palliative care are inadequate to alter the quality and delivery of care provided to patients with cancer.…”
Section: What Is Already Known?mentioning
confidence: 99%
“…Different versions of the ESAS have been used in research studies [9][10][11][12]. Recent studies have indicated that patients may have difficulty understanding the terminology and correct use of the ESAS [9,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%